Method for one-step in-situ preparation of Z-type NiMn2O4 / NiO composite photocatalyst with compact interface and application of Z-type NiMn2O4 / NiO composite photocatalyst

The Z-type NiMn2O4/NiO composite photocatalyst with a tight interface was prepared by chemical precipitation method and in-situ synthesis method, which solved the problem of narrow photoresponse range and intimate interface of the existing photocatalyst, and achieved efficient photocatalytic degradation effect, which was particularly suitable for treating medical antibiotic wastewater.

CN119657164AActive Publication Date: 2025-03-21LIAONING UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411835920.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

When photocatalyzing the degradation of organic pollutants, existing single broadband semiconductor photocatalysts have problems such as narrow photoresponse range, high electron-hole recombination rate, and poor quantum efficiency. The contact interface between Z-type photocatalyst nanoparticles prepared by conventional methods is not tight, which limits electron transmission and leads to insufficient usability.

Method used

The Z-type NiMn2O4/NiO composite photocatalyst with tight interfaces is prepared in situ through chemical precipitation method and in-situ synthesis method, which controls the raw material ratio, calcination temperature and time, ensures a tight interface between nanoparticles and improves electron transport efficiency.

Benefits of technology

The redox capacity and photocatalytic degradation efficiency of photocatalysts are improved, and the degradation capacity of organic pollutants in water is enhanced, especially when treating medical antibiotic wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657164A_ABST
    Figure CN119657164A_ABST
Patent Text Reader

Abstract

The invention relates to a method for one-step in-situ preparation of a Z-type NiMn2O4 / NiO composite photocatalyst with a compact interface and application of the Z-type NiMn2O4 / NiO composite photocatalyst. The preparation method comprises the following steps: firstly, respectively dispersing MnCl2. 4H2O and Ni (NO3) 2.6 H2O in distilled water according to a certain molar ratio, adding a proper amount of NaOH solution into the distilled water, fully stirring to precipitate, and collecting; and uniformly mixing the collected precipitate, filtering, washing, drying, grinding and calcining to form the NiMn2O4 / NiO composite photocatalyst. According to the preparation method, the Z-type NiMn2O4 / NiO composite photocatalyst is prepared in situ through a simple one step, a tight interface is formed between NiMn2O4 and NiO through in-situ construction, and electron transfer of a system is facilitated. The method for preparing the composite photocatalyst is simple and convenient, the effective Z-type obtaining rate is high, the catalyst crystal form structure is good, and organic pollutants in water can be efficiently photocatalytically degraded under sunlight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalysts and their applications, and specifically relates to a method for preparing a tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst in one step in situ by using a chemical precipitation method and an in-situ synthesis method, and its application Background Art

[0002] Chlortetracycline hydrochloride (CTC) is a medical antibiotic that is widely used in disease prevention due to its broad spectrum, strong antibacterial and antiprotozoal activity, and low cost. Since CTC is difficult to digest after ingestion, a large part of CTC will be released into the water as an active drug during metabolism, causing a series of organic pollution problems in water. In recent years, semiconductor-based photocatalytic oxidation technology has received widespread attention in the treatment of organic pollutants in water due to its strong redox ability, high energy efficiency, low cost, and no secondary pollution.

[0003] As a typical transition metal oxide, NiO has a relatively stable and wide bandgap, and is a p-type semiconductor material with great application prospects. It is widely used in the field of photocatalysis for photocatalytic degradation of organic dyes and photoelectrochemical water decomposition. However, among semiconductor photocatalysts, single broadband semiconductor photocatalysts have a narrow light response range and a large number of photogenerated electron-hole (e-hole) gaps. - -h + ) has the disadvantages of high recombination rate and poor quantum efficiency. In order to solve this problem, inspired by the photosynthesis of plants in nature, it is a good choice to use two semiconductor materials to composite and construct a Z-type composite photocatalyst. As a kind of spinel, NiMn2O4 has a band gap of about 2.1eV, which has attracted people's attention due to its narrow band gap and good photocatalytic performance. Therefore, the composite of NiO and NiMn2O4 to construct a Z-type photocatalytic system can not only improve the system's photogenerated e - -h +The separation efficiency of the photocatalyst is improved, and due to the combination of different band gap structures, the light response range is also broadened, thereby greatly improving the activity of the composite photocatalyst. However, when certain conventional methods are used to prepare binary Z-type photocatalysts, there is always an obvious contact interface between the two semiconductor nanoparticles, which limits the transmission of electrons and leads to insufficient availability of the Z-type photocatalyst. In addition, for the preparation of Z-type photocatalysts, how to obtain a high proportion of effective Z-type nanocomposite photocatalysts is the key to improving photocatalytic activity. Therefore, the present invention is based on NiO photocatalysts, and by in-situ constructing a binary Z-type composite photocatalyst with a close interface, it is used to further improve and enhance its photocatalytic activity and explore its catalytic degradation effect on CTC in water. The preparation process of the present invention is ingenious, simple, low-cost, and the composite catalyst has a high acquisition rate and good crystal form. It has a strong degradation ability for both antibiotic wastewater and dye wastewater. The technology is expected to play a role in constructing efficient photocatalysts and using solar light to catalytically degrade organic pollutants in water. Summary of the invention

[0004] The purpose of the present invention is to synthesize a Z-shaped interface-tight NiMn2O4 / NiO composite photocatalyst in one step by controlling the ratio of raw materials, the calcination temperature and time of the preparation process. The preparation process of the present invention is simple and low in cost, and the contact interface between the generated NiMn2O4 and NiO nanoparticles is tight, the NiMn2O4 / NiO composite photocatalyst has a good crystal structure, and the effective Z-shaped structure is obtained at a high rate. This not only improves the redox capacity of the system, but also effectively reduces the photogenerated - -h + The right recombination rate makes full use of sunlight and enhances its photocatalytic degradation ability.

[0005] Another object of the present invention is to utilize Z-type NiMn2O4 / NiO composite photocatalyst to catalyze the degradation of antibiotics in medical wastewater. The technical solution adopted by the present invention is: a one-step in-situ method for preparing a tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst, comprising the following steps:

[0006] (1) A certain proportion of MnCl2·4H2O and Ni(NO3)2·6H2O were dispersed in distilled water, stirred thoroughly, and then a certain amount of NaOH solution was added thereto, stirred for 1.0 h, to obtain a precipitate;

[0007] (2) After the precipitate is uniformly mixed, it is washed, the pH is adjusted to alkaline, the mixed precipitate is collected by centrifugation and filtration, and then dried at 80° C. for 12 h;

[0008] (3) The dried mixed precipitate powder is uniformly ground and then calcined to obtain the target product NiMn2O4 / NiO.

[0009] The above-mentioned one-step in-situ preparation method of the interface tight Z-type NiMn2O4 / NiO composite photocatalyst, in step (1), the optimal molar ratio of Ni 2+ :Mn 2+ =1.0~2.0:1.0.

[0010] The above-mentioned one-step in-situ preparation method of the interface tight Z-type NiMn2O4 / NiO composite photocatalyst, in step (1), the optimal molar ratio of Ni 2+ :Mn 2+ =1.5:1.0.

[0011] In the above-mentioned one-step in-situ method for preparing a tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst, the adjustment to alkalinity is to adjust the pH to 9-10.

[0012] The above-mentioned one-step in-situ method for preparing the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst has a calcination temperature of 800°C and a calcination time of 1.0 to 3.0 hours.

[0013] The application of the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst prepared according to the above preparation method in the degradation of medical antibiotics under sunlight.

[0014] The above application method is as follows: add Z-type NiMn2O4 / NiO composite photocatalyst to a solution containing antibiotics and irradiate it under sunlight for 2.0 to 3.0 hours.

[0015] In any of the above uses, the medical antibiotic is a tetracycline antibiotic.

[0016] In the above application, the tetracycline antibiotic is chlortetracycline hydrochloride.

[0017] In the above application, the concentration of chlortetracycline hydrochloride is 15 mg / L.

[0018] The beneficial effects of the present invention are as follows: the present invention prepares the Z-type NiMn2O4 / NiO photocatalyst by chemical precipitation method and in-situ synthesis method. The preparation method is simple and ingenious, low in cost, and high in the yield of the composite catalyst. It can form a close interface between NiMn2O4 and NiO nanoparticles, and the formed crystal form is good, which is conducive to a high yield of the effective Z-type structure and improves the transmission efficiency of the photogenerated electrons in the system. The construction of the Z-type NiMn2O4 / NiO composite photocatalyst with a close interface can not only effectively utilize sunlight, but also improve the efficiency of the photogenerated electrons in the system. - -h + The separation efficiency is improved, the redox capacity of the system is enhanced, and thus its ability to photocatalytically degrade organic pollutants in water is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the X-ray diffraction pattern of NiMn2O4 nanoparticles.

[0020] Figure 2 This is the X-ray diffraction pattern of NiO nanoparticles.

[0021] Figure 3 This is the X-ray diffraction pattern of NiMn2O4 / NiO composite photocatalyst. DETAILED DESCRIPTION

[0022] Example 1

[0023] (I) Interface tight Z-type NiMn2O4 / NiO composite photocatalyst, the preparation method is as follows:

[0024] First, MnCl2·4H2O and Ni(NO3)2·6H2O were mixed at a certain molar ratio (Ni 2+ :Mn 2+ =1.0:1.0, 1.5:1.0, 2.0:1.0) were dispersed in deionized water respectively, and magnetic stirring was applied for 30 minutes to completely dissolve them. Secondly, an appropriate amount of 1.0 mol / L NaOH solution was added dropwise to the above solutions until the precipitate was completely precipitated. After magnetic stirring for 1.0 h, the precipitate was collected and mixed. The precipitate mixture was fully stirred to make it uniform, and the pH was adjusted to 9-10 and then filtered. The filtered mixed precipitate was dried at 80°C for 12h. After drying, the powder was evenly ground and placed in a muffle furnace for calcination. The products (Ni 2+ :Mn 2+ =1.5:1.0) were marked as NiMn2O4 / NiO(800-1), NiMn2O4 / NiO(800-2), and NiMn2O4 / NiO(800-3), respectively.

[0025] (II) Comparative Example

[0026] Preparation of NiO nanoparticles: First, weigh 2.908g Ni(NO3)2·6H2O and dissolve it in 50mL distilled water and stir it continuously for 30min to dissolve it completely. Add an appropriate amount of 1.0mol / L NaOH solution drop by drop until the precipitate is completely precipitated. Stir it magnetically for 1.0h and let it stand. After the precipitation is complete, remove the supernatant. Wash the precipitate with distilled water until the pH of the washing liquid is 9-10, then collect it by centrifugation. Dry the collected precipitate at 80℃ for 12h. The dried powder is placed in a mortar and ground evenly. The uniform powder is placed in a crucible and calcined in a muffle furnace at 800℃ for 1.0h to obtain NiO nanoparticles.

[0027] Preparation of NiMn2O4 nanoparticles: MnCl2·4H2O and Ni(NO3)2·6H2O in molar ratio (Ni 2+ :Mn 2+ =1.0:2.0) were dispersed in deionized water and magnetically stirred for 30 minutes to completely dissolve. Further, an appropriate amount of 1.0 mol / L NaOH solution was added dropwise to the above solution until the precipitate was completely precipitated, and the solution was allowed to stand after magnetic stirring for 1.0 h. The precipitate was collected and mixed. The precipitate mixture was fully stirred to make it uniform, and the pH was adjusted to 9-10 and then filtered. The filtered mixed precipitate was dried at 80°C for 12h. After drying, the powder was evenly ground and placed in a muffle furnace and calcined at 800°C for 1.0h to obtain NiMn2O4 nanoparticles.

[0028] (III) Characterization of Catalyst

[0029] Figure 1 This is the XRD pattern of NiMn2O4 nanoparticles prepared in comparative example. Figure 1 As shown, the characteristic peaks of NiMn2O4 are obvious and sharp, and are consistent with the standard card (JCPDS 01-1110). This result shows that the present invention successfully prepares NiMn2O4 nanoparticles with good crystal form.

[0030] Figure 2 The XRD pattern of NiO nanoparticles prepared in the comparative example is shown in FIG. Figure 2 As shown, the characteristic peaks of NiO are obvious and sharp, and correspond one to one with the standard card (JCPDS 47-1049), which indicates that the NiO nanoparticles are successfully prepared and have good crystal form.

[0031] Figure 3 This is the XRD pattern of the tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst. Figure 3 As shown, the characteristic peaks belonging to NiMn2O4 and NiO nanoparticles can be observed. The results show that the present invention successfully prepares the NiMn2O4 / NiO composite photocatalyst, and the composite photocatalyst has a good crystal structure.

[0032] Example 2 Application of the tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst in the degradation of medical antibiotics under sunlight (I) Effect of different molar ratios of catalysts on the degradation of chlortetracycline hydrochloride

[0033] Experimental method: A 300W xenon lamp was used as a simulated sunlight source. 1.0g / L NiMn2O4 / NiO composite photocatalyst was added to 100mL CTC solution with an initial concentration of 15mg / L. The solution was irradiated under simulated sunlight for 3.0h, and the supernatant was centrifuged and filtered to determine its absorbance. The degradation rate of CTC was calculated based on its absorbance. The results are shown in Table 1.

[0034] Degradation rate (%) = (1-C t / C0)×100% (where C0: the concentration of CTC in the stock solution; C t : The concentration of CTCs in the sample).

[0035] Table 1 Effect of different molar ratios of catalysts on the degradation rate of chlortetracycline hydrochloride

[0036]

[0037] Table 1 shows that when the molar ratio (Ni 2+ :Mn 2+ )=1.5:1.0, the prepared composite photocatalyst NiMn2O4 / NiO has the best effect on CTC degradation, and the degradation of CTC can reach 78.82% in 3.0h under simulated sunlight.

[0038] (II) Effect of different calcination times of catalyst on the degradation of chlortetracycline hydrochloride

[0039] Experimental method: A 300W xenon lamp was used as a simulated sunlight source. NiMn2O4 / NiO composite photocatalysts with calcination times of 1.0h, 2.0h and 3.0h were added to 100mL of CTC solution with an initial concentration of 15mg / L. The amount of composite photocatalyst added was 1.0g / L. The solution was irradiated under simulated sunlight for 3.0h, centrifuged and the supernatant was taken. The supernatant was then filtered and its absorbance was determined. The degradation rate of CTC was converted according to its absorbance. The results are shown in Table 2.

[0040] Table 2 Effect of catalyst calcination time on the degradation rate of chlortetracycline hydrochloride

[0041]

[0042] It can be seen from Table 2 that when the calcination time is 1.0 h, the prepared NiMn2O4 / NiO(800-1) composite photocatalyst has the best degradation effect on CTC, and its degradation rate is 78.82%.

[0043] (III) Effects of different catalysts on the degradation of chlortetracycline hydrochloride

[0044] Experimental method: The same mass of NiMn2O4, NiO and NiMn2O4 / NiO (800-1) photocatalysts were added to 100mL of CTC solution with an initial concentration of 15mg / L, and the dosage of each catalyst was 1.0g / L. Irradiate under simulated sunlight for 3.0h, centrifuge to take the supernatant, and then filter the supernatant to determine its absorbance. The degradation rate of CTC was converted according to its absorbance. The results are shown in Table 3.

[0045] Table 3 Effect of different catalysts on the degradation rate of chlortetracycline hydrochloride

[0046]

[0047] As shown in Table 3, compared with NiMn2O4 and NiO monomer photocatalysts, the interface-tight Z-type NiMn2O4 / NiO (800-1) composite photocatalyst prepared by the present invention has the best degradation effect on CTC pollutants, and the degradation rate can reach 78.82% under simulated sunlight for 3.0 hours. The above results show that the in-situ constructed Z-type NiMn2O4 / NiO has a high photocatalytic activity, because the tight interface is conducive to the electron transfer between the systems, thereby making the NiMn2O4 / NiO composite photocatalyst have a high redox ability.

[0048] (IV) Effect of illumination time on the degradation rate of chlortetracycline hydrochloride

[0049] Experimental method: A 300W xenon lamp was used as a simulated sunlight source, and 1.0g / L NiMn2O4 / NiO(800-1) composite photocatalyst was added to 100mL of CTC solution with an initial concentration of 15mg / L. Under simulated sunlight, 3.0mL CTC solution was extracted every 30min for centrifugation, filtration and absorbance determination. The degradation rate of CTC was calculated based on its absorbance. The results are shown in Table 4.

[0050] Table 4 Effect of illumination time on the degradation rate of chlortetracycline hydrochloride

[0051]

[0052] It can be seen from Table 4 that the degradation degree of CTC by the NiMn2O4 / NiO(800-1) composite photocatalyst increases with the increase of illumination time. When the illumination time is 180 min, the degradation degree of CTC is the largest, and the degradation rate can reach 78.82%.

[0053] (V) Effect of catalyst recycling on the degradation of chlortetracycline hydrochloride

[0054] Experimental method: A 300W xenon lamp was used as a simulated solar light source, and 1.0g / L of NiMn2O4 / NiO (800-1) composite photocatalyst was added to 100mL of CTC solution with an initial concentration of 15mg / L. Irradiate under simulated sunlight for 3.0h, centrifuge to obtain the supernatant, and then filter the supernatant to determine its absorbance. In addition, the catalyst was collected, rinsed, boiled, and other steps to remove the CTC molecules remaining on its surface, and finally the catalyst was dried for the next experiment. This experiment was repeated 5 times to obtain the degradation of CTC by the NiMn2O4 / NiO (800-1) composite photocatalyst with different usage times. The results are shown in Table 5

[0055] Table 5 Effect of catalyst usage times on the degradation of chlortetracycline hydrochloride

[0056]

[0057] As can be seen from Table 5, the degradation rate of CTC by the composite photocatalyst NiMn2O4 / NiO(800-1) is still as high as 70.15% after being reused for 5 times, indicating that the in-situ constructed interface-tight Z-type NiMn2O4 / NiO(800-1) composite photocatalyst has high reusability.

[0058] In the above embodiments, the medical antibiotic used is chlortetracycline hydrochloride, but the antibiotic degraded in the present invention is not limited to chlortetracycline hydrochloride. The method of the present invention is suitable for degrading medical antibiotics and dye wastewater, etc.

Claims

1. A one-step in-situ method for preparing a tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst, characterized in that: The steps include: (1) A certain proportion of MnCl2·4H2O and Ni(NO3)2·6H2O were dispersed in distilled water, stirred thoroughly, and then a certain amount of NaOH solution was added thereto, stirred for 1.0 h, to obtain a precipitate; (2) After the precipitate is uniformly mixed, it is washed, the pH is adjusted to alkaline, the mixed precipitate is collected by centrifugation and filtration, and then dried at 80° C. for 12 h; (3) The dried mixed precipitate powder is uniformly ground and then calcined to obtain the target product NiMn2O4 / NiO.

2. The one-step in-situ preparation method of the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst according to claim 1 is characterized in that: In step (1), the optimal molar ratio is Ni 2+ :Mn 2+ =1.0~2.0:1.

0.

3. The one-step in-situ preparation method of the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst according to claim 2 is characterized in that: In step (1), the optimal molar ratio is Ni 2+ :Mn 2+ =1.5:1.

0.

4. The one-step in-situ preparation method of the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst according to claim 1 is characterized in that: The adjustment to alkalinity is to adjust pH to 9-10.

5. The one-step in-situ preparation method of the interface-tight Z-type NiMn2O4 / NiO composite photocatalyst according to claim 1 is characterized in that: The calcination temperature is 800°C, and the calcination time is 1.0 to 3.0 hours.

6. Use of a tightly interfaced Z-type NiMn2O4 / NiO composite photocatalyst prepared by the preparation method according to any one of claims 1 to 5 in the degradation of medical antibiotics under sunlight.

7. The use according to claim 6, characterized in that: The method is as follows: add a Z-type NiMn2O4 / NiO composite photocatalyst to a solution containing antibiotics and irradiate the solution under sunlight for 2.0 to 3.0 hours.

8. The use according to claim 7, characterized in that: The medical antibiotics are tetracycline antibiotics.

9. The use according to claim 8, characterized in that: The tetracycline antibiotic is chlortetracycline hydrochloride.

10. The use according to claim 9, characterized in that: The concentration of chlortetracycline hydrochloride is 15 mg / L.

Citation Information

Patent Citations

  • Substrate with photocatalytic coating

    CA2446791A1

  • Preparation method and application of ilmenite-type nickel manganese multiple oxide (NiMnO3)

    CN102583586A

  • Method for preparing lithium-ion battery anode material lithium nickel manganese dioxide (LiNiMnO2)

    CN102723476A

  • Ni-Mn composite oxide catalyst for eliminating benzene-series volatile organic substances from air and preparation method thereof

    CN105126863A

  • Spinel-type catalytic material preparation method

    CN110193368A